2015
DOI: 10.1002/ejhf.458
|View full text |Cite
|
Sign up to set email alerts
|

Predicting heart failure decompensation using cardiac implantable electronic devices: a review of practices and challenges

Abstract: Cardiac implantable electronic devices include remote monitoring tools intended to guide heart failure management. The monitoring focus has been on averting hospitalizations by predicting worsening heart failure. However, although device measurements including intrathoracic impedance correlate with risk of decompensation, they individually predict hospitalizations with limited accuracy. Current ‘crisis detection’ methods involve repeatedly screening for impending decompensation, and do not adhere to the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…A clinical trial conducted by Domenichini et al showed that alert-guided care does not prevent hospitalisation but can help In supporting the patient's well-being and self-assessed quality of life (7) . Moreover, the cost-effectiveness impact on the healthcare system may be beneficial due to implementation of such a solution, where the physician's decisions will be supported by algorithmic remotely gathered findings, but this view will soon be verified according to the rules of evidence-based medicine (8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial conducted by Domenichini et al showed that alert-guided care does not prevent hospitalisation but can help In supporting the patient's well-being and self-assessed quality of life (7) . Moreover, the cost-effectiveness impact on the healthcare system may be beneficial due to implementation of such a solution, where the physician's decisions will be supported by algorithmic remotely gathered findings, but this view will soon be verified according to the rules of evidence-based medicine (8) .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take into account that today modern algorithms and systems allow physicians to predict with high accuracy that an owner of a CRT device will soon become (in 30 days) a patient in their (or another) department (5,8) . To understand the gravity of this fact, one need only consider how many preventive actions can be undertaken during those 30 days to avoid such an event.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent published studies have started to explore the literature on remote monitoring to understand variation in success rates and the inconsistent definition of remote monitoring . The effectiveness of remote monitoring may also depend on the particular monitoring device/system or patient characteristics …”
Section: Introductionmentioning
confidence: 99%
“…cardiac resynchronization therapy devices and implantable defibrillator/cardioverters [8,10]. Furthermore, the clinical outcomes of both phenotypes of HF have been occurred similar or at least not sufficiently distinguished [11] that is important challenge for contemporary medical care service.…”
Section: Introductionmentioning
confidence: 99%